Evaluation of Changes Associated with an Educational Intervention on Basic Life Support and Airway Obstruction Among Schoolchildren Aged from 11 to 18 Years Old in the Island of La Palma (Canary Islands). - Martínez-León, Sofía; Francisco-Sánchez, Alba; Rescalvo-Arjona, Beatriz; Brito-Brito, Pedro Ruymán; Rodríguez-Álvaro, Martín (Nursing Reports, 2026)
Cardiopulmonary arrests are time-dependent emergencies where survival rates are quickly reduced without early intervention. BLS training programmes for teachers and schoolchildren must be mandatory, as they not only improve efficacy when performing the manoeuvres but also enhance willingness to do so. Background/Objectives: To analyse changes in knowledge and whether they are sustained in time after a theoretical–practical intervention led by nurses. To objectively analyse the quality of chest compressions according to the students' group and age. Methods: A quasi-experimental study without a Control Group and with three measuring instances: Baseline (T0), Immediate post-intervention (T1) and at three months (T2). Knowledge was assessed by means of an ad hoc questionnaire; in turn, the chest compressions were evaluated using a mannequin with feedback. The longitudinal changes were analysed based on paired discordant answers. Descriptive analyses according to age and schooling level were performed. Results: There were 982, 756 and 509 students at T0, T1 and T2, respectively. A total of 206 records were paired at all three measuring moments. The intervention was associated with an increase in knowledge test scores, which is preserved at three months. Most of the questionnaire items presented positive changes or remained unchanged. The significant difference was maintained in 8 of the 10 questions. As for the compressions, a significant and positive correlation was found between age and overall score, depth and rate. The comparative analysis between the Lower Secondary Education and Higher Secondary Education groups found significant differences in those same variables, as well as a difference in release. Conclusions: Altogether, the results of this study contribute evidence about the effectiveness of BLS training among adolescents in a real-world context, underscoring the need for ongoing and age-adapted interventions.